Egyptian and imported pottery from the Red Sea port of Mersa Gawsis, Egypt - Wallace-Jones, Sally, (Archaeopress Egyptology ;, 2018)
The unique site of Mersa Gawasis was a base for seaborne trade along the Red Sea coast during the Middle Kingdom. This volume presents the site's wide variety of ceramic material, offering also an interpretation of what pottery reveals about activities at the site.